The Development of eLEMA-SCL Protozoa for Invertebrate Zoology Courses - Haryono, Agus; Basuki, Bejo; Adam, Chaidir; Savitri, Shanty; Araina, Elga; Fahrina, Ririn (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The development of electronic learning materials is very necessary for the midst of the COVID-19 pandemic which requires lecture activities to be carried out online. This was carried out to support physical distancing to break the chain of transmission of COVID-19. Currently, there are not many electronic learning materials available that lead to student-centered learning (SCL) and can be implemented amid the COVID- 19 pandemics. The purpose of this research is to develop an eLEMA (Electronic Learning Material) application, an Android-based electronic learning material with content or material that can be accessed online and offline, and with features that make it easier for users to operate. This research is a research development (Research and Development; R & D) to develop Android-based ELEMA-SCL Protozoa (Electronic Learning Material-Student Centered Learning) for Zoology courses. This development model consists of 3 phases of approach, namely: (1) Phase 1: Needs Assessment; (2) Phase 2: Design; and (3) Phase 3: Develop / Implement. The product developed in the form of an Android-based eLEMA application made using the MIT App Inventor is feasible to implement. The implementation results show: (1) the effectiveness of online and offline lectures with a gain value of 0.52 in the Medium category; (2) student response to the implementation of eLEMA is positive. Thus, the eLEMA application can be used for online and offline lectures during the COVID-19 pandemic.